Magnetostatic pressure as a factor of spiral domain stabilization in ferrite-garnet films - Mamalui, Ju.A.; Siryuk, Ju.A. (Functional Materials, 2008)
Stable spiral domains (SpD) surrounded by bubble lattice (LED) and existing in the absence of magnetic fields have been experimentally studied in epitaxial ferrite-garnet films. Thermodynamic approach and the concept of magnetostatic pressure are used to explain the SpD behavior with bias field (H) and temperature (T) change. It is shown that T- or H-induced phase transitions (PT) in LED initiate PT in SpD. В епітаксійних плівках феритів-гранатів експериментально вивчено стійкі спіральні домени (СпД), які оточені граткою ЦМД (ГЦД) та існуючі при відсутності магнітних полів. Для пояснення поведінки СпД при змінах поля зміщення (Н) або температури (Т) використовується термодинамічний підхід з введенням поняття магнітостатичного тиску. Показано, що індуковані Т або Н фазові переходи (ФП) у ГЦД призводять до ФП у СпД. В эпитаксиальных пленках ферритов-гранатов экспериментально изучены устойчивые спиральные домены (СпД), окруженные решеткой ЦМД (PЦД) и существующие при отсутствии магнитных полей. Для объяснения поведения СпД при изменении поля смещения (Н) или температуры (Т) используется термодинамический подход с введением понятия магнитостатического давления. Показано, что индуцированные Т или Н фазовые переходы (ФП) в PЦД вызывают ФП в СпД.